2012
DOI: 10.5194/amt-5-2581-2012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Single Particle Soot Photometer and Integrating Sphere/Integrating Sandwich Spectrophotometer measurement techniques for quantifying black carbon concentration in snow

Abstract: Abstract. We evaluate the performance of the Single Particle Soot Photometer (SP2) and the Integrating Sphere/Integrating Sandwich Spectrophotometer (ISSW) in quantifying the concentration of refractory black carbon (BC) in snow samples. We find that the SP2 can be used to measure BC mass concentration in snow with substantially larger uncertainty (60 %) than for atmospheric sampling (<30 %). Achieving this level of accuracy requires careful assessment of nebulizer performance and SP2 calibration with consider… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
184
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(199 citation statements)
references
References 25 publications
9
184
2
Order By: Relevance
“…Ohata et al (2011) and Schwarz et al (2012) also observed larger rBC particle size in rain and snow, respectively, than in the atmosphere. This fact suggests that the transference between phases (aerosol-hydrosol) may modify the interaction between BC particles and promote coagulation, or that larger particles containing more BC mass are preferentially wet-scavenged.…”
Section: Single-particle Soot Photometermentioning
confidence: 99%
See 3 more Smart Citations
“…Ohata et al (2011) and Schwarz et al (2012) also observed larger rBC particle size in rain and snow, respectively, than in the atmosphere. This fact suggests that the transference between phases (aerosol-hydrosol) may modify the interaction between BC particles and promote coagulation, or that larger particles containing more BC mass are preferentially wet-scavenged.…”
Section: Single-particle Soot Photometermentioning
confidence: 99%
“…Kaspari et al (2011) estimated 50% losses of particles during the process of nebulizing water samples. The efficiency of the nebulizer is also size dependent; for instance, Schwarz et al (2012) reported lower nebulization efficiency (<10%) for larger particles (∼600 nm). Another issue that potentially affected the concentration of rBC measured by the SP2 was the storage time (15-30 days for this analysis).…”
Section: Single-particle Soot Photometermentioning
confidence: 99%
See 2 more Smart Citations
“…Immediately after melt, the liquid was sonicated and filtered through quartz fiber filters (Supplemental Materials) (Schwarz et al, 2012;Wang et al, 2012). BC and OC on the filters were measured using a method similar to the IMPROVE protocol (Cao et al, 2003;Chow et al, 2004).…”
Section: Samples and Methodsmentioning
confidence: 99%